Rencana dan Strategi Peningkatan Kesadaran Hukum Masyarakat - Ahmad, Ibrahim (Universitas Gorontalo, 2018)
In Article 1 paragraph (3) of the Constitution of the Republic of Indonesia affirmed that Indonesia is a State of law. Based on the phrase it would be appropriate and reasonable if every citizen of the Republic of Indonesia must have a high legal awareness. The legal consciousness is the awareness that every human being has of what the law is or what the law should be, a certain category of our psychic life by which we distinguish between the law (recht) and not thelaw (onrecht), between what should be done and not necessarily done. Awareness of what the law means is the awareness that the law is a protection of human interest, because the lawis a method whose function is to protect human interests. Thus the legal counseling program towards the creation of legal awareness has a very urgent and strategic role. Therefore, legal education programs in various forms, whether oral orwritten, are urgently required to be realized simultaneously by every agency or institution, whether executive, legislative or judicial. Legal counseling programs should be conducted in various area so flaw, both in civil law, criminal law and in the field of constitutional law, as well as in the field of state administration law. Furthermore, the implementation of early counseling programs through formal educational institutions in all strata needs to be done and encouraged optimally. The benchmark so fthesuccess of the expected law-conscious villages based on the expected conditions as mentioned above are as follows: The creation of national stability in general, The creation of legal objectives of legal certainty, justice, benefit and public order, Public trust to the government is very high, The life of a safe and peaceful society, and the level of community economy is increasing and equitable.